Pelatihan Pengembangan Kemampuan Membuat Konten Kreatif Digital Bagi Penyelenggara Yayasan Al Muhajir Bandung Raya - Djuwita, Amalia; Milyane, Tita Melia; Sutamto, Tatto (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
In the current era of digital technology, people carry out social interactions and seek information based on the internet network. This change in people's lifestyles, if it is not accompanied by knowledge about how to use digital media correctly and appropriately and does not violate the ethics that apply in society and how to create creative content that has appeal and has a positive impact, then the use of digital media will not effective. The Al Muhajir Bandung Raya Foundation, as a legal entity social institution that operates in the social, educational and religious fields, is currently experiencing obstacles in its operations. One of the obstacles to running the Foundation is that it does not have adequate resources that can manage digital media properly and appropriately. In fact, in the digital era, the problem of using digital media to support the existence and business of an institution is to become supporting capital for the continuity of the institution. To assist the Foundation's needs in producing professional staff in the field of digital creative content, the Digital Public Relations Abdimas Team plans to hold training activities to develop the ability to create digital creative content for the organizers of the Al Muhajir Foundation, Bandung Raya with partners targeting the management and stakeholders in the foundation.